Insomnia Symptoms and Daytime Function in Stable Heart Failure - Redeker, Nancy S. (Associated Professional Sleep Societies, LLC, 2010)
OBJECTIVES: To evaluate insomnia symptoms and the extent to which they are associated with clinical and demographic patient characteristics, daytime symptoms, and functional performance in patients with stable heart failure (HF). DESIGN: Cross-sectional, observational. SETTING: Five structured HF disease management programs in the Northeastern U.S. PARTICIPANTS: 173 stable chronic HF patients INTERVENTIONS: N/A MEASUREMENTS AND RESULTS: Full polysomnography was obtained for one night in participants' homes. Participants completed the six-minute walk test, Medical Outcomes Study SF-36, Epworth Sleepiness Scale, Pittsburgh Sleep Quality Index, Multi-Dimensional Assessment of Fatigue Scale, Centers for the Epidemiological Studies of Depression Scale, and questionnaire items eliciting insomnia symptoms (self-reported difficulty initiating and maintaining sleep and waking too early in the morning). Over half of HF patients reported insomnia symptoms. These were associated with increased daytime symptoms (depression, fatigue), excessive daytime sleepiness, and functional performance in models that statistically controlled for clinical and demographic covariates. These relationships were not explained by sleep disordered breathing. CONCLUSIONS: Insomnia symptoms are common in patients with stable heart failure and are associated with daytime symptoms and decrements in functional performance. CITATION: Redeker NS; Jeon S; Muench U; Campbell D; Walsleben J; Rapoport DM. Insomnia symptoms and daytime function in stable heart failure. SLEEP 2010;33(9):1210-1216.